1994
DOI: 10.1111/j.1432-2277.1994.tb01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Does concommitant splenectomy raise the mortality of liver transplant recipients?

Abstract: Within a 17-month period, 130 orthotopic liver transplantations were performed in our hospital. Nine of these were retransplantations and were not included in our analysis. In the remaining 121 patients, splenectomy was performed in 34 patients, either synchronously with the transplant procedure (27 patients) or in the postoperative period (7 patients). Indications for splenectomy were lienalis-steal syndrome in 15 patients and hypersplenism in 15 cases. The number of rejection episodes was fairly equal in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 8 publications
(2 reference statements)
0
19
3
4
Order By: Relevance
“…Even though we have not yet encountered severe infections related to splenectomy, we have to consider a vaccination plan for those recipients. Warfarin is Lusebrink et al 23 reported that there was a marked difference in the frequency of infectious episodes (61.7% versus 25.3%) that resulted in a decreased survival rate (77.5% versus 95.4%) for splenectomized deceased donor liver transplant recipients. Although we need close long-term follow-up for A-LDLT recipients who have undergone splenectomy, our univariate analysis for the short term has demonstrated that splenectomy does not have a negative impact on patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we have not yet encountered severe infections related to splenectomy, we have to consider a vaccination plan for those recipients. Warfarin is Lusebrink et al 23 reported that there was a marked difference in the frequency of infectious episodes (61.7% versus 25.3%) that resulted in a decreased survival rate (77.5% versus 95.4%) for splenectomized deceased donor liver transplant recipients. Although we need close long-term follow-up for A-LDLT recipients who have undergone splenectomy, our univariate analysis for the short term has demonstrated that splenectomy does not have a negative impact on patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…This has prompted the authors to revise the name of splenic artery steal syndrome to splenic artery syndrome, thereby underlining that the cause is portal hyperperfusion and not arterial siphon [121] . Most recently, a retrospective analysis of 650 orthotopic liver transplantations has revealed an incidence of 5.1% for splenic artery syndrome [122] , which is well within the range of the estimated incidence of artery splenic syndrome of 3.1%-11.5% after orthotopic liver transplantation [117,118,123,124] . Prophylactic treatment with ligation of the splenic artery for all patients at risk for development of splenic artery syndrome is recommended and effectively prevents splenic artery syndrome [122] .…”
Section: Surgical Interventions For Modification Of the Habrmentioning
confidence: 97%
“…Выполнение спленэктомии пациентам, перенес-шим ОТП, при проявлении гиперспленизма или SASS помимо рисков, связанных непосредственно с оперативным вмешательством, может приводить к таким серьезным осложнениям, как сепсис, коа-гуляционные расстройства (тромбозы и тромбоэм-болии, в т. ч. сосудистых конструкций, выполнен-ных во время ОТП), иммунологические нарушения [1][2][3]. ЭСА является альтернативой спленэктомии, по данным разных авторов выполняется у 1-3% па-циентов, может выступать в качестве первого этапа лечения и при достижении клинического эффекта позволяет избежать необходимости спленэктомии [3,4,6].…”
Section: Discussionunclassified
“…ЭСА является альтернативой спленэктомии, по данным разных авторов выполняется у 1-3% па-циентов, может выступать в качестве первого этапа лечения и при достижении клинического эффекта позволяет избежать необходимости спленэктомии [3,4,6]. Наиболее часто ЭСА сопровождается бо-лями в левой половине живота и лихорадкой (пост-эмболизационный синдром) [3,12]. В нашей серии эти симптомы в разной степени присутствовали у всех пациентов, что требовало проведения анти-биотикопрофилактики, назначения анальгетиков, в т. ч. наркотических.…”
Section: Discussionunclassified
See 1 more Smart Citation